Synthesis, сharacterization, and сatalytic properties of GdCoO3 for dry reforming of methane - Allabergenova Regina K.; Вobkova Daria А.; Borodina Elizaveta M.; Kryuchkova Tatiana A.; Markova Ekaterina B.; Sheshko Tatiana F.; Lobanov Nikolai N.; Cherednichenko Alexander G. (Journal of the Serbian Chemical Society, 2024)
Perovskite oxides (ABO3) due to their high thermal stability and the ability to control the physico-chemical properties are considered as an alternative to traditional catalysts containing noble and transition metals. Herein, the recent research breakthroughs of GdCoO3 catalysts in experimental studies are summarized in detail. First, the perovskite-type GdCoO3 complex oxides were obtained by co-precipitation method with the various precipitators and were characterized by X-ray diffraction (XRD), low temperature nitrogen adsorption and IR spectroscopy. Physical and chemical analysis showed that the choice of precipitant doesn’t significantly affect the phase composition of the perovskites. The catalytic performance of gadolinium cobaltites was discussed. It was found that the use of cobaltites obtained by co-precipitation leads to the inhibition of the side reaction of the reverse steam reforming of carbon monoxide. Finally, the investigation of the used catalysts demonstrated the formation of Gd2O2CO3 and metallic cobalt, which indicates the nature of active centres: gadolinium is the centre of CO adsorption, while hydrogen chemisorption occurs on cobalt-sites.